A simple method to estimate noise levels in the workplace based on self-reported speech communication effort in noise. (3rd July 2019) - Ferguson, Melanie A.; Tomlinson, Kezia B.; Davis, Adrian C.; Lutman, Mark E.
Abstract: Objective: To validate a method using self-reported speech communication effort in noise to estimate occupational noise levels by comparing with measured noise levels. Design: A comparative observational study. Reported vocal effort to communicate with a person at a distance of 1.2 m during workplace-related tasks was used to provide an estimate of noise levels in the workplace. These estimated noise levels were compared against noise level measurements obtained using personal noise dosimetry badges for corresponding tasks undertaken by participants. Study sample: Participants ( n = 168) aged 16–25 years were recruited from companies where workplace noise levels were at least 85 dB(A). Results: Estimated noise levels using speech communication ability were evenly distributed above and below the measured noise levels ( n = 134), indicating a lack of systematic bias in the method. For 91% of participants, estimates of noise levels using speech communication were within ±6 dB of the measured levels, whilst 56% were within ±3 dB. Conclusions: Report of speech communication effort required in noise by employees is an effective method of estimating noise levels within the workplace. This can be used for retrospective noise level assessment where there are no recorded noise level measurements, such as for retrospective research studies or in medicolegal work.